Emotional and Instrumental Support Provision Interact to Predict Well-Being - Morelli, Sylvia A. (Emotion, 2015)
Individuals in close relationships help each other in many ways, from listening to each other’s problems, to making each other feel understood, to providing practical support. However, it is unclear if these supportive behaviors track each other across days and as stable tendencies in close relationships. Further, although past work suggests that giving support improves providers’ well-being, the specific features of support provision that improve providers’ psychological lives remain unclear. We addressed these gaps in knowledge through a daily diary study that comprehensively assessed support provision and its effects on well-being. We found that providers’ emotional support (e.g., empathy) and instrumental support represent distinct dimensions of support provision, replicating prior work. Crucially, emotional support, but not instrumental support, consistently predicted provider well-being. These two dimensions also interacted, such that instrumental support enhanced well-being of both providers and recipients, but only when providers were emotionally engaged while providing support. These findings illuminate the nature of support provision and suggest targets for interventions to enhance well-being.